Biomechanical insights into carbon plate geometry in running shoes in male runners: implications for sprint performance and ankle stability - Teng, Jin; Pan, Meixi; Han, Yingfeng; Diaz-Cidoncha Garcia, Jorge; Yi, Qing; Shen, Siqin (Frontiers in Bioengineering and Biotechnology, 2026)
To date, limited evidence exists on how carbon plate geometry influences sprint biomechanics. This study investigated the biomechanical effects of different carbon plate configurations in running shoes on sprint performance and lower-limb stability. Forty trained male sprinters performed submaximal sprinting at a controlled speed of 7 m s-1 while wearing shoes equipped with either a full-length carbon plate (FC) or a Y-shaped carbon plate (YC). Kinematic and kinetic data were collected using a motion capture system and force platform. Outcome measures included spatiotemporal variables, joint kinematics (hip, knee, ankle and metatarsophalangeal joint angles), and kinetics (vertical and horizontal ground reaction force and joint moment). Differences between the two shoe conditions were examined using paired-sample t-tests, while Statistical Parametric Mapping was applied to detect time-dependent differences across the stance phase. YC shoes demonstrated a higher peak vertical impact force, increasing from 2.90 to 3.14 BW (mean difference: 0.24 BW; Cohen’s d = 0.49; p = 0.003). Statistical Parametric Mapping further revealed sustained force elevations during 38%–65% of the stance phase (p < 0.001). In contrast, FC shoes demonstrated greater ankle eversion and reduced metatarsophalangeal extension (p < 0.001), suggesting FC shoes may improve energy efficiency but elevate eversion-related injury risk. In addition, YC shoes increased sagittal-plane ankle range of motion from 39.3° to 43.5° (mean difference: 4.2°; Cohen’s d = 0.75; p < 0.001), suggesting improved joint mobility demands during sprinting. These findings demonstrate that variations in carbon plate geometry lead to distinct alterations in lower-limb mechanical responses during sprinting in male runners, with different implications for force output, joint motion, and ankle control. This biomechanical evidence may assist in optimizing carbon plate design to balance sprint performance demands with ankle stability considerations.